Gi- and Gq-coupled ADP (P2Y) receptors act in opposition to modulate nociceptive signaling and inflammatory pain behavior - Molliver Derek C; Malin Sacha A (SAGE Publishing, 2010)
Abstract Background Investigations of nucleotide signaling in nociception to date have focused on actions of adenosine triphosphate (ATP). Both ATP-gated ion channels (P2X receptors) and G protein-coupled (P2Y) receptors contribute to nociceptive signaling in peripheral sensory neurons. In addition, several studies have implicated the Gq-coupled adenosine diphosphate (ADP) receptor P2Y1 in sensory transduction. In this study, we examined the expression and function of P2Y1 and the Gi-coupled receptors P2Y12, P2Y13 and P2Y14 in sensory neurons to determine their contribution to nociception. Results We detected mRNA and protein for ADP receptors P2Y12 and P2Y13 in mouse dorsal root ganglia (DRG). P2Y14, a homologous Gi-coupled nucleotide receptor, is also expressed in DRG. Immunohistochemical analysis of receptor distribution indicated that these receptors are widely expressed in nociceptive neurons. Using ratiometric calcium imaging, we found that ADP evokes increases in intracellular calcium in isolated DRG neurons and also produces a pertussis toxin-sensitive inhibition of depolarization-evoked calcium transients. The inhibitory effect of ADP was unaltered in the presence of the selective P2Y1 antagonist MRS2179 and in neurons isolated from P2Y1 knockout mice, whereas ADP-evoked calcium transients were greatly reduced. Analysis of behavioral responses to noxious heat before and after inflammatory injury (injection of complete Freund's adjuvant into the hindpaw) revealed that P2Y1 is required for the full expression of inflammatory hyperalgesia, whereas local injection of agonists for Gi-coupled P2Y receptors reduced hyperalgesia. Conclusions We report that Gi-coupled P2Y receptors are widely expressed in peripheral sensory neurons. Agonists for these receptors inhibit nociceptive signaling in isolated neurons and reduce behavioral hyperalgesia in vivo. Anti-nociceptive actions of these receptors appear to be antagonized by the Gq-coupled ADP receptor, P2Y1, which is required for the full expression of inflammatory hyperalgesia. We propose that nociceptor sensitivity is modulated by the integration of nucleotide signaling through Gq- and Gi-coupled P2Y receptors, and this balance is altered in response to inflammatory injury. Taken together, our data suggest that Gi-coupled P2Y receptors are broadly expressed in nociceptors, inhibit nociceptive signaling in vivo, and represent potential targets for the development of novel analgesic drugs.